The introduction of the new health care procedure for the Czech market - Havran, Adam; Lhotáková, Markéta, 1971-; Cook, Gina, 1970-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
The objective of this work is to analyse the possibility of use of micro -- needles technology as the method of drug delivery in the Czech Republic. The characteristics of this product (application, connection with drug, etc.) suggest three possible target groups: patients, health care providers or pharmaceutical companies. One of the goals is to analyse legal requirements on such products, evaluate current market situation and according to this information choose the best group for the product consumption. Also product itself presents a challenge and there are several designs of micro -- needle or needleless drug applicators. Combined together, this study aims to find, whether is the Czech market able to accept new method of drug delivery, in which form and how can patient reach this technology.
Vedoucí práce: Markéta Lhotáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses